Uncanny Adaptations: Revisionary Narratives in Bryan Fuller's Hannibal. (29th November 2018) - Raines, Melissa
Abstracts: This article examines the prevalence of the uncanny in Bryan Fuller's Hannibal (2013–15 ), the television adaptation of Thomas Harris's Hannibal Lecter novels and their subsequent film versions. While Linda Hutcheon has proposed the concept of 'knowing' and 'unknowing' audiences in relation to adaptations, popular awareness of Hannibal Lecter and representation of the character as psychopathic complicate this dichotomy, allowing Fuller to play with a broader familiarity with character, incident, and context within a relatively unfamiliar prequel setting. Analysis of individual scenes and details from the final shooting scripts demonstrate the uncanny destabilizations created by the series' forensic adaptations of crime and untraditional family structures, as well as Hannibal's complex characterization. I argue that as we as viewers experience our pre-established familiarity with Hannibal in this unsettlingly unfamiliar context, and as we come to know the doctor within the world of the series, this evolving familiarity is repeatedly challenged in a way that also challenges our conceptions of empathy.